2016
DOI: 10.1039/c6an01352j
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the influence of trace impurities on ionization of atmospheric noble gas dielectric barrier discharges

Abstract: While the influence of trace impurities in noble gas discharges is well established in theoretical work, experimental approaches are difficult. Particularly the effects of trace concentrations of N on He discharges are complicated to investigate due to the fact that for He 5.0 the purity of He is only 99.999%. This corresponds to a residual concentration of 10 ppm, thereof 3 ppm of N, in He. Matters are made difficult by the fact that He DBD plasmajets are normally operated under an ambient atmosphere, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…From [19], it was also observed that there is a minimum threshold for the helium mole fraction in the helium jet for the successful propagation of the plasma bullet. Recently many important experimental studies have been carried out providing very good insight into the characterization and understanding of these devices, the electric fields [20][21][22][23][24][25] and the different produced species [26][27][28][29][30][31]. However, in order to increase the understanding behind the operation of APPJ and to overcome some of the practical experimental limitations, numerical modelling has been increasingly used to simulate APPJ devices.…”
Section: Introductionmentioning
confidence: 99%
“…From [19], it was also observed that there is a minimum threshold for the helium mole fraction in the helium jet for the successful propagation of the plasma bullet. Recently many important experimental studies have been carried out providing very good insight into the characterization and understanding of these devices, the electric fields [20][21][22][23][24][25] and the different produced species [26][27][28][29][30][31]. However, in order to increase the understanding behind the operation of APPJ and to overcome some of the practical experimental limitations, numerical modelling has been increasingly used to simulate APPJ devices.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to atmospheric pressure chemical ionization (APCI), dielectric barrier discharges (DBDs) have become a suitable ionization source for several types of applications. In addition to having soft ionization capabilities, these discharges can also be used for atomic absorption spectroscopy (AAS) and optical emission spectroscopy (OES) when modified. Thus, DBDs are highly versatile. Detailed studies have increased knowledge about fundamental discharge mechanisms in noble gas discharges at atmospheric pressure, which have led to further improvements in the use of these discharges. , Flexible microtube plasma (FμTP), being a small, easy, and safe-to-handle discharge, is the result of this optimization. Because of its small dimensions and flexible nature, it can be incorporated without major effort into existing setups.…”
mentioning
confidence: 99%
“…Detailed studies have increased knowledge about fundamental discharge mechanisms in noble gas discharges at atmospheric pressure, which have led to further improvements in the use of these discharges. 24,25 Flexible microtube plasma (FμTP), being a small, easy, and safe-tohandle discharge, is the result of this optimization. Because of its small dimensions and flexible nature, it can be incorporated without major effort into existing setups.…”
mentioning
confidence: 99%
“…Adding other reaction or collision partners leads to different reactions, and the minimum ignition voltage will change. Other mechanisms resulting in, e.g., the protonation of analyte molecules, are also interfered by these changes 24 .…”
Section: Introductionmentioning
confidence: 99%